Oleg and Vladimir Presnyakov’s postmodern play with the Bible - Tyka, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article presents an attempt to discuss the place and the role of the Bible in Oleg and Vladimir Presnyakov`s oeuvre on the example of Before the Flood. The author places the meaning of the symbols, motives, pictures and Biblical codes in the postmodernist context. The main aim of this measure is to present a multilevel and typical of postmodernist esthetic play (with) cultural text undertaken by the Russian playwrights in their experimental writing. The literary reinterpretation of the Biblical events and figures allows not only for stressing the intertextual character of the discussed literary work but also for demonstrating lack of the basic moral principles and identity dominant in the Brothers` literary world, the progressing relativism of values, alienation and human`s degradation in the surrounding material world as well as unskilfulness terming and defining our own emotional states.